EVA1B to Evaluate the Tumor Immune Microenvironment and Clinical Prognosis in Glioma - Qu, Shanqiang; Liu, Jin; Wang, Huafu (Frontiers in Immunology, 2021)
Background: Previous research indicated that the tumor cells and microenvironments interactions is critical for immunotherapeutic response. However, how to predict the clinical response to immunotherapy remains a dilemma for clinicians. Hence, this study aimed to investigate the associations between EVA1B expression and prognosis and tumor-infiltrating immune cells in glioma. Methods: Firstly, we detected the EVA1B expression in glioma tissues through biological databases. The chi-squared test, Kaplan-Meier, and univariate and multivariate Cox regression analyses were used to analyze the clinical significance of EVA1B expression. The correlation between EVA1B expression and levels of tumor-infiltrating immune cells in glioma tissues was investigated. Receiver operating characteristic (ROC) analysis was performed to compare the predictive power between EVA1B and other commonly immune-related markers. Results: Through the CGGA cohort of 325 glioma patients, we found that EVA1B was upregulated in glioma, and increased with tumor grade. High EVA1B expression was prominently associated with unfavorable clinciopathological features, and poorer survival of patients, which were further confirmed by TCGA (n=609) and GEO (n=74) cohorts. Furthermore, multivariate analysis indicated that EVA1B is an independent prognostic biomarker for glioma. Importantly, EVA1B overexpression was associated with higher infiltration level of CD4+ T cells, CD8+ T cells, B cells, macrophages and neutrophils in glioma. ROC curves showed that, compared with PD-L1, CTLA-4 and Siglec15, EVA1B presented a higher are under the curve (AUC) value (AUC=0.824) for predicting high immune infiltration levels in glioma. Conclusions: We found that EVA1B was upregulated and could act as a poor prognostic biomarker in glioma. Importantly, EVA1B overexpression was associated with immune infiltration levels of immune cells including B cells, CD4+ T cells, CD8+ T cells, macrophages and neutrophils, and strongly with the overall immune infiltration levels of glioma. These findings suggested that EVA1B might be a potential biomarker for evaluating prognosis and immune infiltration in glioma.